Adverse Effects of Ultra-Loose Monetary Policies on Investment, Growth and Income Distribution - Andreas Hoffmann; Gunther Schnabl (Center for Economic Studies and ifo Institute (CESifo), 2016)
The paper analyses adverse investment, growth and distributional effects of ultra-loose monetary policies based on the monetary overinvestment theories of Hayek and Mises. We argue that ultra-loose monetary policies create incentives to substitute real investment by financial investment. When interest rates are expected to fall in the long term, the marginal and average efficiency of investments fall along, dampening GDP growth. We further show that the prolonged period of very low interest rates tends to distribute income towards higher income classes. This helps explain why consumer price inflation in most advanced economies does not pick up despite unprecedented monetary expansions.
Keywords: E52; E58; F42; E63; 330; Hayek; Mises; monetary overinvestment theory; asymmetric monetary policy; financial crisis; marginal productivity of investment; secular stagnation